Dual strategies for Argonaute2 mediated biogenesis of erythroid miRNAs underlie conserved requirements for slicing in mammals - Jee, David (Mol Cell, 2018)
While Slicer activity of Argonaute is central to RNAi, conserved roles of Slicing in endogenous regulatory biology are less clear, especially in mammals. Biogenesis of erythroid Dicer-independent mir-451 involves Ago2 catalysis, but mir-451-KO mice do not phenocopy Ago2 catalytic-dead (Ago2-CD) mice, suggesting other needs for Slicing. Here, we reveal mir-486 as another dominant erythroid miRNA with atypical biogenesis. While it is Dicer-dependent, it requires Slicing to eliminate its star strand. Thus, in Ago2-CD conditions, miR-486-5p is functionally inactive due to duplex arrest. Genomewide analyses reveal miR-486 and miR-451 as the major Slicing-dependent miRNAs in the hematopoietic system. Moreover, mir-486-KO mice exhibit erythroid defects, and double knockout of mir-486/451 phenocopies cell-autonomous requirements of Ago2-CD in the hematopoietic system. Finally, we observe that Ago2 is the dominant-expressed Argonaute in maturing erythroblasts, reflecting a specialized environment for processing Slicing-dependent miRNAs. Overall, the mammalian hematopoietic system has evolved multiple conserved requirements for Slicer-dependent miRNA biogenesis.